Identifikasi Jenis Tumbuhan dari Famili Asteraceae Di Kawasan Wisata Irenggolo Kediri - Ida Rahmawati; Tutut Indah Sulistiyowati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2021)
Irenggolo is a waterfall tourism area located in the Wilis Mountains. This area has a fairly good diversity of flora, one of which is Asteraceae family. This family has very divers in members. Research on Asteraceae plants in this area never been carried out. The purpose of this study was to determine the type of plants from the Asteraceae family that live in the Irenggolo Kediri. Methode for sampling using Visual Encounter Survey technique in four different areas. Observation results obtained 13 species of plants from Asteraceae family with three tribes, that are Sphagneticola trilobata, Galinsoga parviflora, Crassocephalum crepidioides, Cosmos sulphureus, Tagetes erecta, Sonchus wightianus, Conyza bonariensis, Ageratum conyzoides, Dahlia pinnata, Bidens pilosa, Zinnia elegans, Chromolaena odorata, serta Eupatorium capillifolium.